(untitled) (Bangladesh Pharmaceutical Journal, 2018)
A large number of people in Bangladesh suffer from many cardiovascular diseases (CVDs). Therefore, cardiovascular drugs are one of the major classes of drugs prescribed in Bangladesh. The study of prescribing patterns seeks to monitor, evaluate and suggest modifications in clinicians’ prescribing habits to make medical care more rational. This study was mainly focused on the recent trends of prescribing patterns of oral cardiovascular drugs in Dhaka city. It was a questionnaire-based direct interview type of descriptive study, conducted in the cardiology departments of eight most renowned hospitals of Dhaka, during the study period of February 2017 to April 2017. Most patients in the disease states belonged to the older age group of 50-60 years. More male patients were found in the cardiology departments than the female patients. Hypertension was the most prevalent diseases (86.67%) followed by angina (75.00%) and myocardial infarction (53.33%). Most commonly prescribed antihypertensive medication was angiotensin-II receptor blocker (ARB, 55.00%) and individually losartan (61.67%), followed by angiotensin-converting enzyme inhibitor (ACEI, 25.00%) and only ramipril (90.00%). Amlodipine was the first choice of every respondent when prescribing a calcium-channel blocker (CCB). In case of combination products, amlodipine plus atenolol was found to be the most preferred (65%) medication, followed by hydrochlorothiazide plus losartan (40%). Bangladesh Pharmaceutical Journal 21(2): 123-130, 2018